1991
DOI: 10.1002/jmv.1890340202
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distribution of human rotavirus serotypes 1, 2, 3, and 4 in venezuelan children with gastroenteritis during 1979–1989

Abstract: The temporal distribution and clinical severity of rotavirus VP7 serotypes 1, 2, 3, and 4 recovered from 427 Venezuelan children with acute gastroenteritis over a period of 11 years were studied. Rotavirus VP7 serotype was established by ELISA serotyping in 298 (69.78%) of the specimens while the serotype of the remaining 129 (30.21%) samples could not be determined. Of the specimens typed, 85 (19.90% of the total) were serotype 1, 43 (10.07%) were serotype 2, 105 (24.59%) were serotype 3, and 65 (15.22%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
13
0
4
Order By: Relevance
“…Previous serological studies conducted in Venezuela have demonstrated temporal variation in the predominant circulating of RV G serotype, but in general G1, G3, or G4 and moderate rates of circulation of G2 strains have been detected [White et al, 1991;Pérez-Schael et al, 1999]. This study shows that G3P[8]/ NSP4-E1 was the most common RV genotype combination detected in strains circulating in Valencia, Venezuela, in 2003.…”
Section: Discussionmentioning
confidence: 56%
“…Previous serological studies conducted in Venezuela have demonstrated temporal variation in the predominant circulating of RV G serotype, but in general G1, G3, or G4 and moderate rates of circulation of G2 strains have been detected [White et al, 1991;Pérez-Schael et al, 1999]. This study shows that G3P[8]/ NSP4-E1 was the most common RV genotype combination detected in strains circulating in Valencia, Venezuela, in 2003.…”
Section: Discussionmentioning
confidence: 56%
“…While variability in G serotypes from one rotavirus season to another is known and long-term surveys are required to correctly evaluate the relative frequencies of rotavirus G serotypes, there are a few studies showing that a serotype other than G1 was the most prevalent among long-term surveys performed over five years or more. Serotype G3 was predominant in India (32.5%) (3) and in Venezuela (24.6%) (73). Serotype G4 was the most prevalent in Malaysia (41.5%) (56) and Bangladesh (32.5%) (64).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus-positive specimens were serotyped by monoclonal antibody ELISA as previously described [Flores et al, 1988;White et al, 1991]. The monoclonal antibodies used for serotyping were generously obtained from Drs.…”
Section: Rotavirus Antigen Detection and Serotypingmentioning
confidence: 99%